ChemInform Abstract: Mixed AggregAte (MAA): A Single Concept for All Dipolar Organometallic Aggregates. 1. Structural Data. Issue 48 (26th November 2013) - Harrison‐Marchand, Anne; Mongin, Florence
Abstract Review: structures of organo(bi)metallic species; 826 refs.